Croma kid [videorecording (DVD)] - Chea, Pablo; Cárdenas, Israel, 1980-; Cárdenas, Israel, 1980-; Cárdenas Guzmán, Bosco; Piña Gautier, Jaime; Bogaert, Nashla; Maler, David (Burning Bulb Publishing, 2025)
Like many teens, Emi is a little embarrassed by his eccentric family, especially now that they're launching a low-budget magic show on local TV in 1993. But when a glitch in their DIY gear accidentally opens a portal to another dimension and his parents vanish into the multiverse, Emi must channel all his techie know-how to bring them back. Blending the spirit of late-analog family adventure films with the quirky charm of analog-era aesthetics, Croma Kid is a heartfelt and whimsical tribute to Rubik's Cubes, cassette tapes, Betacam, and the wild, neon-soaked imagination that painted the end of the last millennium. This feature is presented in its original Spanish language with closed captions in Spanish and English.